Cutting edge technologies for the evaluation of Plant-based food and meat Quality: A Comprehensive review - Nurul Alam, AMM; Hashem, MA; Matar, AM; Ali, MS; Monti, JA; Hossain, MJ; Yusuf, HM; Mia, N (Meat Research, 2024)
Assessing the food quality is essential to confirm the safety, nutritional value, and sensory attractiveness of the food we ingest. Due to the globalization of food industry and concerns over food security have resulted to a greater demand from consumers for safe and nutritious food. As a result, there is a need for manufacturers to develop cutting edge technologies for recognizing and determining food quality. Presently, stakeholders in the food industry encounter the challenge of ensuring food quality and safety. Producers need to meet sustainable and environmentally robust food production standard, extended shelf life, sensory quality, nutritional value, and functional properties. The general analytical practices identify the primary metabolites for whole food quality which solely verifies the total composition of nutritional metrics. In present days consumers concentrate of functional quality of food items. So, it is essential to examine secondary metabolite compounds, enzymes and other functional quality, authenticity of food items, sources that are critical for health, development, safety, and other aspects of consumer well-being. This review paper seeks to examine the different aspects of evaluating food quality and the methods used to ensure that the food we consume meets the required criteria. Furthermore, it discusses cutting edge technologies for assessing especially secondary metabolites, enzyme functions, functional quality of food items, verifying food authenticity to optimize food manufacturing processes.